51-3x=10x+22

Simple and best practice solution for 51-3x=10x+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 51-3x=10x+22 equation:


Simplifying
51 + -3x = 10x + 22

Reorder the terms:
51 + -3x = 22 + 10x

Solving
51 + -3x = 22 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
51 + -3x + -10x = 22 + 10x + -10x

Combine like terms: -3x + -10x = -13x
51 + -13x = 22 + 10x + -10x

Combine like terms: 10x + -10x = 0
51 + -13x = 22 + 0
51 + -13x = 22

Add '-51' to each side of the equation.
51 + -51 + -13x = 22 + -51

Combine like terms: 51 + -51 = 0
0 + -13x = 22 + -51
-13x = 22 + -51

Combine like terms: 22 + -51 = -29
-13x = -29

Divide each side by '-13'.
x = 2.230769231

Simplifying
x = 2.230769231

See similar equations:

| -5+6(x-3)=15x+3-9x | | -9(t+2)=54 | | 0.5x-0.3(10-3x)=-0.6(x-5) | | 13=13 | | 1/6x-3=5 | | -7/8v=35 | | 3+y/2=3y/4-2 | | x^2+10x+98=0 | | 6+6x=42+x | | -14-9=12 | | 6(a-7)+20=2(a-7) | | 5(5x-3)+5=-9 | | -22u+-1x= | | 9x-3=6x+39 | | 4-4x=-2x-12 | | 18-3x=-9x | | 3(y+2)=30 | | -4x=-35+3x | | -10-3x=-4x+4 | | -0.2j=-0.2 | | 4+0.16n=3 | | 74=-3+2(-3+2) | | 320=10(x+15)-30 | | -x+31=2x-14 | | 8-2x=-32-6x | | 6y+15=3-2y | | -3(2u-x)-4(x+4u)= | | (x+3)(2x-5)=40 | | -12=(-7)-3.5s | | 2(3x-4)=5(x+7) | | 41=-7x+2(x+8) | | 19+2x=-37+6x |

Equations solver categories